Analyses of the energy sources used by Turkish referees during ninety minutes soccer match - (:unkn) unknown (My University, 2013)
The purpose of this study was to predict the percentages of various energy sources used by volunteer 5 official soccer Turkish Referees (mean age: 38.40 ± 1.1 years, height: 178 ± 0.5 cm, body mass: 85.20 ± 2.5 kg) and to analyze the locomotor motions during 90min amateur soccer a match expressed in anaerobic threshold level (ATL). Each subject's heart rate was monitored during a match using a short-range radio telemetry (Sport Tester™ PE3000), and was sampled at 5-s intervals.Percentage of heart rate (x= 181.8 beats/min) and estimated anaerobic threshold level (x= 171.2 beats/min). The locomotor movements (walking, jogging, fast running, backward running and sideway running) of each subjects were recorded on the field by using hand-notational system for whole match period. The frequency and duration of each activity were recorded and these data were utilized to calculate the distance covered by the referee. The result indicated that the mean work ratio below A.T.L. was 77.04%, there was no significant differences between heart rates recorded in the first and second halves and the mean value of total distance covered was 6166 meter; significant fall in the work rate was noted in the second half (p<.05). According the results of this study referees doesn't need vigorous training for officiating a match. But they should participate in aerobic conditioning programs on regular basis and also should be abrupt acceleration and deceleration, charges of direction and angles runs. Additionally, muscle glycogen levels should not be lowered by strenuous activities the day before or the morning of soccer match to be officiated.
Keywords: Anaerobic threshold; Movement-analysis; Radio telemetry; Referees' heart rate; Soccer